Effects of Wi-Fi Radiation on Metabolism of Rat Immature Seminiferous Tubules Ex Vivo - Pinto, Patrícia Feliciano (2017)
In recent decades, several studies have shown a decline in male fertility. As wireless technologies, which use Wi-Fi, and the time spent with them are increasing, the relationship between these two facts has been a subject of investigation. There are several articles that demonstrate the negative consequences of electromagnetic radiation of wireless devices on male fertility, affecting sperm parameters: reducing motility and viability, increasing the percentage of spermatozoa with an abnormal morphology and decreasing sperm concentration. There are also studies that show that the electromagnetic radiation of these devices enhances oxidative stress and increases reactive oxygen species, and is also capable of causing histopathological changes in the male reproductive organs and even alter the production of hormones important for male fertility, such as testosterone. However, all studies show flaws in the design of a realistic model of radiation exposure and there are no studies concerning the effects of electromagnetic radiation on testicular metabolism. A normal reproductive function is affected by the process of spermatogenesis, which in turn is dependent on the testicular metabolism, more specifically the Sertoli cells that provide nutritional support. These cells, located within the seminiferous tubules, in normal situations, metabolize the majority of glucose into lactate, with lactate being the preferred substrate for developing germ cells to obtain energy. However, some studies have already demonstrated in specific circumstances, Sertoli cells may use other substrates instead of glucose to obtain energy. To carry out the study, an exposure set up was developed with different electronic components commercially available to expose the seminiferous tubules in culture, in a realistic way to the electromagnetic radiation. For the validation of the developed set up, spermatozoa of adult mice were exposed for 1 hour to the electromagnetic radiation of the apparatus. From this experiment the results showed a significant decrease in sperm motility of the exposed group comparing to the control group, validating the model. From the metabolism study performed, exposing seminiferous tubules from 20-day-old rats to the built equipment, our results showed that electromagnetic radiation significantly decreased glucose consumption, however, contradictly lactate production increased significantly. The lactate dehydrogenase activity was evaluated and although not significant, the electromagnetic radiation caused an increase. Contradictory results between glucose consumption and lactate production suggest that, when exposed to electromagnetic radiation from Wi-Fi devices, cells responsible for testicular metabolism, namely Sertoli cells in the seminiferous tubules, may use alternative metabolic pathways to produce lactate and consequently obtain energy. In conclusion, this study showed that the exposure model was successfully created and validated and that electromagnetic radiations from Wi-Fi equipment, in addition to causing negative changes in the sperm parameters of the cells, promote changes in normal glycolytic metabolism, suggesting the use of an alternative way of obtaining energy which may have effects on spermatogenesis and affect male fertility.